Consumo de alcohol y sustancias psicoactivas en adolescentes mestizos e indígenas de la parroquia Urdaneta, del cantón Saraguro de la provincia de Loja. - Barrera Barrera, Yosselyn Briggette (2016)
The present research work is descriptive-transversal, with the following general objective: Identify and describe the consumption of alcohol and psychoactive substances in mestizo and indigenous adolescents; And as specific objectives; Characterize the profile of adolescents; Analyze the age of onset of consumption, the scale of consumption according to the different substances, according to age, gender and nationality and examine the risk factors and protectors of adolescents consuming alcohol and psychoactive substances. Based on the results obtained after the Survey on Alcohol Consumption and Psychoactive Substances, it was obtained that the adolescents surveyed correspond to 229 students who met the exclusion and inclusion criteria, alcohol consumption in males constitutes 50, 49% in mestizos and 50.00% in indigenous people; And in the female sex to 32.00% in the mestizas and 34.48% in the indigenous women; In addition a moderate use of psychoactive substances was observed, which are more used in men especially of mestizo nationality; The average age of onset in men is 8.80% at 17 years and in women 4.81% at 16 years; For psychoactive substances the age of onset in men is between 16 and 18 years according to the substance with the exception of ecstasy which was observed 0.80% at 13 years and for women the onset of consumption of psychoactive substances is 1, 92% the 16 years in both mestizo and indigenous nationality; Among the relevant risk factors is the ease of access to substances 27.94%; Lack of participation in preventive activities 63.76%; As predominant protective factors are good relationships with relatives 60.26%. KEY WORDS: Consumption of substances, adolescents, mestizos, indigenous.